Co‐action of COP1, SPA and cryptochrome in light signal transduction and photomorphogenesis of the moss Physcomitrium patens. (22nd February 2023) - Kreiss, Melanie; Haas, Fabian B.; Hansen, Maike; Rensing, Stefan A.; Hoecker, Ute
SUMMARY: The Arabidopsis COP1/SPA ubiquitin ligase suppresses photomorphogenesis in darkness. In the light, photoreceptors inactivate COP1/SPA to allow a light response. While SPA genes are specific to the green lineage, COP1 also exists in humans. This raises the question of when in evolution plant COP1 acquired the need for SPA accessory proteins. We addressed this question by generating Physcomitrium Ppcop1 mutants and comparing their visible and molecular phenotypes with those of Physcomitrium Ppspa mutants. The phenotype of Ppcop1 nonuple mutants resembles that of Ppspa mutants. Most importantly, both mutants produce green chloroplasts in complete darkness. They also exhibit dwarfed gametophores, disturbed branching of protonemata and absent gravitropism. RNA‐sequencing analysis indicates that both mutants undergo weak constitutive light signaling in darkness. PpCOP1 and PpSPA proteins form a complex and they interact via their WD repeat domains with the VP motif of the cryptochrome CCE domain in a blue light‐dependent manner. This resembles the interaction of Arabidopsis SPA proteins with Arabidopsis CRY1, and is different from that with Arabidopsis CRY2. Taken together, the data indicate that PpCOP1 and PpSPA act together to regulate growth and development of Physcomitrium. However, in contrast to their Arabidopsis orthologs, PpCOP1 and PpSPA proteins execute only partial suppression of light signaling in darkness. Hence, additional repressors may exist that contribute to the repression of a light response in dark‐exposed Physcomitrium. Significance Statement: During the water‐to‐land transition in evolution, plants had to adapt to drastically altered light conditions. Here, we investigate the mechanisms that placed the increased plant complexity evolving during terrestrialization under the control of ambient light. Moreover, our findings address when in evolution the activity of the ubiquitin ligase COP1 became dependent on the SPA accessory proteins and cryptochrome.